Physical-mental health and awareness of HIV/STIs among men who have sex with men in selected cities of India - Suraj Pal; Praveen Kumar Pathak; Margubur Rahaman (BMC, 2023)
Abstract Background Men who have Sex with Men being sexual minorities are a vulnerable section of society and are at greater risk of ill-treatment if they are 'out of the closet' regarding their sexuality. Previous evidence suggests that they experienced heightened susceptibility to physical and mental illnesses owing to widespread discrimination and victimization across different walks of life, particularly in developing countries. However, there is a paucity of sound data and scientific understanding related to linkages between physical-mental health and awareness about Human Immunodeficiency Virus/Sexually Transmitted Infections among Men who have Sex with Men in the Indian context. Methods Using a mixed-method approach, the present study examined the association between physical-mental well-being and awareness of comprehensive Human Immunodeficiency Virus/Sexually Transmitted Infections/relevant health behaviours based on primary data collected from 300 respondents from six selected metro cities in India. Descriptive statistics, chi-square test and binary logistic regression model have been used for the quantitative data analyses. In-depth interviews were conducted to contextualize and appreciate the substantive meanings and significance coming out from the quantitative results with the lived experiences of the study respondents. Results Finding suggests that one-fourth of the respondents were experiencing long-term illnesses while close to four out of ten respondents experienced short-term illnesses. About one-third of the respondents experienced disordered eating behaviour and mood swings. Close to one-fifth of the respondents reportedly contemplated suicidal thoughts. Awareness related to Sexually Transmitted Infections and preventive measures related to Human Immunodeficiency Virus risk was considerably low among Men who have Sex with Men. Conclusion Awareness about sexual and reproductive health issues among Men who have Sex with Men needs to be strengthened to curtail the disproportionate risk and vulnerability of Human Immunodeficiency Virus and Sexually Transmitted Infections. The public healthcare system needs to be sensitized and upgraded to cater user-friendly quality healthcare services, without any discrimination against sexual minorities including Men who have Sex with Men. Furthermore, generating public awareness about gender and sexuality-related matters and reducing stigma and discrimination is critical for achieving the health-related sustainable development goals in India without leaving no one behind.